Le Musée à l’École: Une Expérience de Jeu Dramatique par les Oeuvres d’Art - Chaîné, Francine (Theatre Research in Canada / Recherches théâtrales au Canada, 2000)
When works of art are brought into the school, students are given the opportunity to closely examine these art objects and, as it were, to make them their own; the young people become acquainted with the artists who produced the works of art and can both express their opinions about these creations and communicate their ideas to others. Students thus interact with the works themselves. When art becomes the starting point for dramatic play, the experience has the effect of making art come alive. In other words, students communicate with works of art through play, giving these works a new life, one which each student discovers in the drama workshop. We put together an exhibit of landscape paintings which we chose from among the collection of works on loan from the Musée du Québec. The exhibit took place in the fall of 1998 in an elementary school in Rimouski. My paper will deal with this unique experience: I wish to analyse, among other things, what this daily contact with figurative and abstract works of art evoked within the students, both from the point of view of dramatic play and as seen in the comments that were made and the questions that were asked. Like Alice in Wonderland, students ranging from pre-school age all the way up to the sixth grade were invited to interact with a work of art, to make it their own and to give it new life through drama activities. Though this experiment is basically of an interdisciplinary nature, it mainly revolves around dramatic play, enhanced by works of art which are meant to open up new horizons for the students involved. Quand les œuvres entrent à l’école, c’est l’occasion pour les élèves de regarder, d’apprivoiser, de faire connaissance avec les artistes qui les ont produites, d’affirmer ses préférences et de les communiquer aux autres. C’est la réception des œuvres. Quand les œuvres deviennent le point de départ au jeu dramatique, c’est ce que nous nommons l’animation des œuvres. En d’autres mots, il s’agit d’aller à leur rencontre d’un point de vue ludique afin de leur donner une nouvelle vie, celle que chaque joueur découvre en atelier d’art dramatique. Nous avons mis sur pied une exposition de peintures ayant pour thème le paysage; nous les avons choisies dans la collection du Prêt d’œuvres d’art du Musée du Québec. L’exposition a été présentée à l’automne 1998 dans une école primaire de Rimouski. Ce texte porte sur cette expérience singulière; elle vise à analyser entre autres ce que le contact quotidien avec les œuvres figuratives ou abstraites a évoqué chez les élèves tant du point de vue du jeu dramatique que des commentaires et des questionnements qu’elles ont soulevés. À la manière d’Alice, les élèves du préscolaire à la sixième année ont donc été invités à entrer dans l’image afin de se l’approprier et de l’animer dans des activités dramatiques. Bien que cette expérience ait un caractère interdisciplinaire, elle est principalement centrée sur le jeu dramatique avec le support des œuvres d’art qui agissent comme révélateur auprès des joueurs.